Albania's Integration Process to NATO: Resolving Internal Security Problems as Balkan Penninsula Countries - Mohamad Fajar Haqi Ismaya; Raesita Rakhmawati Rosadi (JURNAL POLINTER : KAJIAN POLITIK DAN HUBUNGAN INTERNASIONAL, 2022)
As a Balkan peninsula country regionally threatened by the instability of security, Albania made an effort to upgrade its state's security alliances in the region. In June 1992, Albania started to apply for membership in NATO. This step recognizes Albania as the first former Balkan state to become the most significant Trans-Atlantic security alliance. Afterward, Albania took the role of NATO's representative to uphold peace and stability. Inexact period, former Balkan states had suffered from arm conflict, terrorism movement, and security instability. Through Albania, NATO successfully had its representative to further respond to security problems in the region. However, internal stability problems in Albania became other challenges as its state joined NATO membership. Albania also utilizes NATO's transfer of knowledge to improve its country's capacity, especially in several key cooperation aspects.